PENGARUH MEDIA ANIMASI AUDIO VISUAL TERHADAP PERSEPSI DAN KEMAMPUAN PEMAHAMAN KONSEP SISWA PADA PELAJARAN IPS KELAS V - Fadilah Idris; Nursalam; Muhlis Madani (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2022)
The purpose of the study was to analyze the ability to understand social studies concepts in fifth grade students; analyzing student learning perceptions through audio-visual animation learning; and to determine the effect of audio-visual animation media on the ability to understand concepts and perceptions of class V students. This type of research is Quasi Experimental Design in this study given certain treatments (treatment), namely the control class and the experimental class. The sample in this study is part of the population with the sampling technique is purposive sampling. Data collection methods used are motivation questionnaires and learning outcomes tests and documentation. The data analysis technique used is the first by using a descriptive statistical approach, prerequisite test, and Manova hypothesis testing. The results of the study, test the Manova hypothesis on the multivariate test that the significance value of audio-visual animation media on students' motivation and learning outcomes is 0.000 <0.05 then H1 is accepted and Ho is rejected, and then the Tests of Between-Subjects Effects test is carried out with a significance value of influence Audio visual animation media on students' perception and understanding of social studies concepts is 0.000, which means a significance value of 0.000 <0.05, which means that H1 is accepted and Ho is rejected with the conclusion that there is a significant effect of audio-visual animation media on perception and understanding ability. Social studies concept material types and economic activities of the community in class V. Keyword : audio visual, concept understanding, perception